Lembaga Pendidikan Dalam Alquran - Firdaus Syah (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Educational institutions are one of the most important factors that must be understood about the nature of their existence. Many people think that educational institutions are only in the form of schools or madrasah. Even though schools or madrasah are only one type of formal educational institution that exists. Al-Qur'an which is the holy book of Muslims in which there are various complete life guidelines including regulating educational issues. In the Qur'an there are special terms that refer to the meaning of educational institutions. To find out more about the concept of Islamic educational institutions according to the Qur'an, more in-depth research is needed by examining word for word related to the term so that the true nature of Islamic educational institutions can be well known. The method used in this research is literature review, in this case the researcher examines from various sources, especially the Qur'an and is enriched with hadith and the opinions of scholars and experts. The results of the study can be concluded that the educational institutions contained in the Qur'an are family, madrasah and society.